Monitoring the difference in liquid levels in adjacent tanks - Zhukov, B.V.; Odnovo, A.V. (Radiotekhnika, 2021)
The possibility of synchronous monitoring of coolant levels in the cooling systems of nuclear and thermal power plants before and after the barrier mesh using a specialized level gauge is considered. The block diagram of a level gauge providing current synchronous control of liquid levels in two adjacent channels (reservoirs), as well as the difference in liquid levels in them, is presented. A feature of the structural diagram of a specialized acoustic level gauge is the use of a radiation source common to both channels and a device for dividing the common waveguide path into two channels. An algorithm for the functioning of a specialized level gauge has been developed, in which, based on time diagrams, it is shown how the level is controlled in each channel and the difference in liquid levels before and after the barrier grid is calculated. The description of the algorithm is accompanied by calculated expressions for determining the levels and the difference in liquid levels. For a level gauge made in the acoustic wavelength range, a condition is given that is necessary for the creation of a device that provides matching when dividing a common channel into two independent channels of pulse signal propagation. This condition made it possible to establish the relationship between the inner diameters of cylindrical pipes used as waveguide paths of an acoustic wave. Variants of the implementation of a specialized level gauge based on two modifications of the ZOND-3M level gauge are proposed, in which cylindrical pipes are used as waveguiding systems. It is shown that when using the AP-7VT transceiver, the level gauge will have an operating range of up to 10m with a level resolution of ± 1mm, and when using the AP-70T transceiver, it will have an operating range of up to 20m with a level resolution of ± 1cm.